Pirfenidone Inhibits Hypoxic Pulmonary Hypertension through the NADPH/ROS/p38 Pathway in Adventitial Fibroblasts in the Pulmonary Artery - Song Zhang; ZongXiu Yin; WeiDong Qin; XiaoLi Ma; Yao Zhang; EnXiu Liu; YanBiao Chu (Mediators of Inflammation)
Hypoxic pulmonary hypertension (HPH) is a devastating disease characterized by progressive vasoconstriction and vascular remodeling. Pirfenidone (PFD) inhibits the progression of HPH, though the molecular mechanisms remain unknown. This study is aimed at determining the role and mechanism of PFD in HPH in human pulmonary artery adventitial fibroblasts (HPAAFs), which were cultured under normal or hypoxic conditions. NOX4 and Rac1 were inhibited or overexpressed by shRNA or pcDNA3.1, respectively. Proliferation of HPAAFs was quantified by colorimetric 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assays to assess cellular metabolic activity, cell counts, and ethynyldeoxyuridine (EdU) assays to detect DNA synthesis. Migration of HPAAFs was assessed by a wound healing assay. The expression levels of smooth muscle alpha-actin (a-SMA) and procollagen I (COL1A1) were assessed by RT-PCR and western blot analysis. PFD suppressed hypoxia-induced proliferation and migration of HPAAFs. Compared with the hypoxic control group, PFD reduced the expression of a-SMA and procollagen I (COL1A1). PFD reduced hypoxia-induced phosphorylation of p38 through the NOX4/reactive oxygen species (ROS) signaling pathway. Moreover, Rac1 also decreased hypoxia-induced phosphorylation of p38, without any cross-interaction with NOX4. These findings demonstrate that PFD is a novel therapeutic agent to prevent cell proliferation, migration, and fibrosis, which might be useful in inhibiting vascular remodeling in patients with HPH.